Gene expression profiling in uveal melanoma: technical reliability and correlation of molecular class with pathologic characteristics - Kristen M. Plasseraud; Jeff K. Wilkinson; Kristen M. Oelschlager; Trisha M. Poteet; Robert W. Cook; John F. Stone; Federico A. Monzon (BMC, 2017)
Abstract Background A 15-gene expression profile test has been clinically validated and is widely utilized in newly diagnosed uveal melanoma (UM) patients to assess metastatic potential of the tumor. As most patients are treated with eye-sparing radiotherapy, there is limited tumor tissue available for testing, and technical reliability and success of prognostic testing are critical. This study assessed the analytical performance of the 15-gene expression test for UM and the correlation of molecular class with pathologic characteristics. Methods Inter-assay, intra-assay, inter-instrument/operator, and inter-site experiments were conducted, and concordance of the 15-gene expression profile test results and associated discriminant scores for matched tumor samples were evaluated. Technical success was determined from de-identified clinical reports from January 2010 - May 2016. Pathologic characteristics of enucleated tumors were correlated with molecular class results. Results Inter-assay concordance on 16 samples run on 3 consecutive days was 100%, and matched discriminant scores were strongly correlated (R2 = 0.9944). Inter-assay concordance of 46 samples assayed within a one year period was 100%, with an R2 value of 0.9747 for the discriminant scores. Intra-assay concordance of 12 samples run concurrently in duplicates was 100%; discriminant score correlation yielded an R2 of 0.9934. Concordance between two sites assessing the same tumors was 100% with an R2 of 0.9818 between discriminant scores. Inter-operator/instrument concordance was 96% for Class 1/2 calls and 90% for Class 1A/1B calls, and the discriminant scores had a correlation R2 of 0.9636. Technical success was 96.3% on 5516 samples tested since 2010. Increased largest basal diameter and thickness were significantly associated with Class 1B and Class 2 vs. Class 1A signatures. Conclusions These results show that the 15-gene expression profile test for UM has robust, reproducible performance characteristics. The technical success rate during clinical testing remains as high as first reported during validation. As molecular testing becomes more prevalent for supporting precision medicine efforts, high technical success and reliability are key characteristics when testing such limited and precious samples. The performance of the 15-gene expression profile test in this study should provide confidence to physicians who use the test's molecular classification to inform patient management decisions.